O-Quinone methides via oxone-mediated benzofuran oxidative dearomatization and their intramolecular cycloaddition with carbonyl groups: an expeditious construction of the central tetracyclic core of integrastatins, epicoccolide A, and epicocconigrone A - More, Atul A.; Ramana, Chepuri V. (Organic Letters, 2016)
The intramolecular cycloaddition of o-quinone methides (o-QMs) with a carbonyl group has been envisaged and executed successfully in the context of constructing the complex and rare [6,6,6,6]-tetracyclic core found in the integrastatins, epicoccolide A, and epicocconigrone A. These transient o-QMs were generated easily from the oxidative dearomatization of the corresponding C2-(aryl)benzofuran by employing Oxone in acetone-water at rt. The subsequent cydoaddition with the carbonyl (or conjugated olefin) present on the C2-aryl group was spontaneous.